Title : the efectiveness of using pictures to improve teaching reading comprehension to year 6 pupils in Sekolah Kebangsaan Tempinis, Besut, Terengganu / Abdul Mubin Mohammad - Mohammad, Abdul Mubin (2002)
This study sets out to find out the effectiveness of using pictures to improve teaching reading comprehension to Year 6 pupils in Sekolah Kebangsaan Tempinis Besut Terengganu. In this study, the instruments used were observation, questionnaires and discussions. Information was collected and being discussed for these activities. The respondents were 45 pupils from Year 6 of Sekolah Kebangsaan Tempinis Besut. A study was conducted among these pupils. The result of this study, showed that using pictures are effective to improve teaching reading comprehension to the pupils of Year 6 in Sekolah Kebangsaan Tempinis.